(untitled) (Journal of the College of Basic Education, 2025)
Museums of all types and forms are centers that reflect the cultural, architectural, and artistic background of any society. Their security is of utmost importance, as museums are a vital place for preserving human heritage and all the cultural achievements that humanity has contributed to society throughout the ages. Therefore, a high level of security must be provided, using all means, including concerted community and financial efforts, to contribute to preserving this heritage from vandalism, theft, or intentional or unintentional tampering. Today, the international community is turning its attention to providing everything necessary to protect and secure museums worldwide and developing a comprehensive insurance system for museums and their staff, considering these places a cultural institution and a cultural and scientific monument for every society worldwide. Hence, the importance of this research in highlighting the most important measures and means that must be available to protect museums from any vandalism or theft, ensuring the continuity and preservation of these cultural centers of cognitive value to humanity.